Basics, Uses, and Problems of Guidance and Counseling Teachers in Schools - Nila Frischa Panzola; Neviyarni S; Yarmis Sukur (Journal Of Psychology, Counseling And Education, 2025)
The person responsible for implementing guidance and counseling services in schools is the guidance and counseling teacher/counselor. Guidance and counseling instructors have full obligations, accountability, power and rights to provide guidance and counseling services to students in accordance with established guidelines. A counselor is also an educator, namely a professional whose job is to: (1) determine the needs of students or clients; (2) create a guidance and counseling service program at school; (3) implementing guidance and counseling service programs; and (4) assessing how the program is implemented, (5) evaluating the implementation of the guidance and counseling program using guidance and counseling teacher assessment data. This instructor has all the rights, obligations, authority and duties in guidance and counseling activities for 150 students. Students can find their identity, adapt to their surroundings, and make plans for the future with the help of guidance and counseling services provided by the school. Regarding problems and potential fixes, the problem is. The problems and solutions are as follows: There are still guidance and counseling teachers who do not recognize and fulfill their obligations. The first step in overcoming this problem is to educate and enlighten guidance and counseling teachers about their roles and responsibilities in the classroom. 2) strengthen the desire for improvement among guidance and counseling educators.